PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BCA KCU MAGELANG - Josafat Eleazar Surya (Jurnal Ilmu Manajemen, 2022)
Human resources are an important factor for companies to operate. Human resources have a major contribution to the existence of the organization through its overall performance. Human resources that are not considered by the company can have a negative impact on the sustainability of the company. This research was conducted to show that organizational culture and work environment affect the overall performance of workers either partially or simultaneously. This research was conducted at a company engaged in banking in Magelang City. The population in this study were all employees who had permanent employee status and the respondents were forty-seven respondents. The primary data source is in the form of a questionnaire that contains a chart of various statements related to variable indicators and is compiled using a Likert scale. The results of the research conducted indicate that organizational culture and work environment affect the overall performance of workers, either partially or simultaneously. The limitation of this study is that online data collection makes researchers less flexible in finding and obtaining information. In future research, it is hoped that researchers can further explore the potential relationship between variables in this study.